Quantification of mRNA Using Competitive RTPCR with Standard-Curve Methodology - Shaw-Jenq Tsai; Milo C. Wiltbank (BioTechniques)
The use of reverse transcription polymerase chain reaction (RT-PCR) with internal RNA competitive standards (competitors) provides a means for measuring absolute amounts of mRNA transcripts in small numbers of cells. Most quantitative competitive (QC)-RT-PCR methods require analysis of multiple reactions to determine the equimolar point of the products produced from mRNA vs. competitor RNA. Herein, we present a method to produce one standard curve for each assay with all unknown samples compared directly to this standard curve. The standard curve is produced with differing amounts of standard RNA (native) amplified with one constant amount of competitor RNA. The number of transcripts in an unknown sample mRNA can be directly determined by RT-PCR of the sample with the same amount of competitor RNA and comparison of the ratio of products to the standard curve. This method has been used to quantify expression of multiple gene products from cultured cells or limited amounts of tissues and was found to be straightforward, sensitive, repeatable and quantitative. A complete protocol for producing standard and competitor RNA, subsequent QC-RTPCR steps, and the evaluation of accuracy, sensitivity and precision for this assay are described using bovine prostaglandin F2α receptor mRNA as an example.